(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
To mitigate the problem of loosing data, which can be very crucial to prevent environmental disasters, we proposed a faultÂ tolerant event detection algorithm in a distributed environment. We considered the data loss because of node failure inÂ sensor network due to some technical fault or energy issues. This algorithm works by backing up the data of cluster headsÂ at some secondary nodes. If the secondary node that is backup cluster head notices the failure of primary or vital clusterhead,Â it will inform this to all non cluster-head nodes through pivotal messages. Subsequently, backup cluster-head willÂ start working as vital cluster-head with new backup cluster-head. We have taken all parameters with the promising optimalÂ use of energy. We have compared our results with the existing Dynamic Static Clustering Protocol (DSC) and fault toleranÂ Dynamic Clustering Protocol (FT-DSC). We have compared results on the basis of various parameters like energyÂ consumption over time, number of data packet transmission and network life time based on network remaining energy.